2020
DOI: 10.1891/vv-d-19-00122
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Utilization Patterns Among Children With a History of Child Protective Services Investigations

Abstract: PurposeExamine whether children with a prior child protective services (CPS) investigation had different healthcare utilization compared to children without a history of CPS investigations.MethodsThe Children's Health Assessment and Planning Survey assessed 6,492 primary caregivers of children ages 0–17 years residing in North Texas in 2015. Caregivers reported prior CPS investigations and child healthcare utilization (emergency department [ED] use, unmet medication needs, and unmet medical care needs).Princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Alternatively, students with disabilities, due to their higher levels of need, may disproportionately benefit from the increased resources, supervision, and health care services that are provided in foster care. CPS‐involved children have high rates of inadequately detected and untreated physical, developmental, and mental health problems (Carr et al, 2020; Crozier & Barth, 2005), and—despite real concerns about the quality and consistency of therapeutic services (Szilagyi et al, 2015)—children in foster care are more likely than their in‐home counterparts to receive assessment and treatment. This may also explain why, in our study, the benefits of foster care were concentrated among White children, as studies have consistently found that Black children receive fewer mental health services, even in foster care, irrespective of their need (Garland et al, 2003; Leslie et al, 2004; McMillen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, students with disabilities, due to their higher levels of need, may disproportionately benefit from the increased resources, supervision, and health care services that are provided in foster care. CPS‐involved children have high rates of inadequately detected and untreated physical, developmental, and mental health problems (Carr et al, 2020; Crozier & Barth, 2005), and—despite real concerns about the quality and consistency of therapeutic services (Szilagyi et al, 2015)—children in foster care are more likely than their in‐home counterparts to receive assessment and treatment. This may also explain why, in our study, the benefits of foster care were concentrated among White children, as studies have consistently found that Black children receive fewer mental health services, even in foster care, irrespective of their need (Garland et al, 2003; Leslie et al, 2004; McMillen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%